Large granular lymphocyte leukemia serum and corresponding hematological parameters reveal unique cytokine and sphingolipid biomarkers and associations with STAT3 mutations. (25th July 2020) - Olson, Kristine C.; Moosic, Katharine B.; Jones, Marieke K.; Larkin, Paige M. K.; Olson, Thomas L.; Toro, Mariella F.; Fox, Todd E.; Feith, David J.; Loughran, Thomas P.
Abstract: Large granular lymphocyte (LGL) leukemia is a rare hematological disorder with expansion of the T‐cell or natural killer (NK) cell lineage. Signal transducer and activator of transcription 3 (STAT3) exhibits somatic activating mutations in 30%‐40% of LGL leukemia cases. Transcriptional targets of STAT3 include inflammatory cytokines, thus previous studies have measured cytokine levels of LGL leukemia patients compared to normal donors. Sphingolipid metabolism is a growing area of cancer research, with efforts focused on drug discovery. To date, no studies have examined serum sphingolipids in LGL leukemia patients, and only one study compared a subset of cytokines between the T‐LGL and NK‐LGL subtypes. Therefore, here, we included both LGL leukemia subtypes with the goals of (a) measuring serum sphingolipids for the first time, (b) measuring cytokines to find distinctions between the subtypes, and (c) establishing relationships with STAT3 mutations and clinical data. The serum analyses identified cytokines (EGF, IP‐10, G‐CSF) and sphingolipids (SMC22, SMC24, SMC20, LysoSM) significantly different in the LGL leukemia group compared to normal donors. In a mixed STAT3 mutation group, D661Y samples exhibited the highest mean corpuscular volume (MCV) values. We explored this further by expanding the cohort to include larger groups of single STAT3 mutations. Male D661Y STAT3 samples had lower Hgb and higher MCV compared to wild type (WT) or Y640F counterparts. This is the first report examining large groups of individual STAT3 mutations. Overall, our results revealed novel serum biomarkers and evidence that D661Y mutation may show different clinical manifestation compared to WT or Y640F STAT3. Abstract : Analysis of LGL leukemia serum identified cytokines (EGF, IP‐10, G‐CSF) and sphingolipids (SMC22, SMC24, SMC20, LysoSM) that were significantly different compared to normal donors. Comparing three groups of STAT3 mutation status (WT, Y640F, D661Y) in LGL leukemia patients showed the D661Y mutation group had higher mean corpuscular volume and lower hemoglobin compared to the other groups.